Attending community-based lung cancer screening influences smoking behaviour in deprived populations. (January 2020) - Balata, Haval; Traverse-Healy, Liam; Blandin-Knight, Sean; Armitage, Christopher; Barber, Philip; Colligan, Denis; Elton, Peter; Kirwan, Marie; Lyons, Judith; McWilliams, Lorna; Novasio, Juliette; Sharman, Anna; et al.
Highlights: In this study, one-year smoking quit rate was 10.2%. 55% of quitters attributed stopping directly to their Lung Health Checks. Successful quitting was associated with increased baseline symptoms. There was no evidence of a 'licence to smoke' effect from lung cancer screening. Abstract: Objectives: The impact of lung cancer screening on smoking is unclear, especially in deprived populations who are underrepresented in screening trials. The aim of this observational cohort study was to investigate whether a community-based lung cancer screening programme influenced smoking behaviour and smoking attitude in socio-economically deprived populations. Material and Methods: Ever-smokers, age 55–74, registered at participating General Practices were invited to a community-based Lung Health Check (LHC). This included an assessment of respiratory symptoms, lung cancer risk (PLCOm2012 ), spirometry and signposting to stop smoking services. Those at high risk (PLCOM2012 ≥1.51%) were offered annual low-dose CT screening over two rounds. Self-reported smoking status and behaviour were recorded at the LHC and again 12 months later, when attitudes to smoking were also assessed. Results: 919 participants (51% women) were included in the analysis (77% of attendees); median deprivation rank in the lowest decile for England. At baseline 50.3% were current smokers. One-year quit rate was 10.2%, quitting was associated with increased baseline symptoms (adj OR 2.62, 95% CI 1.07–6.41; p = 0.035) but not demographics or screening results. 55% attributed quitting to the LHC. In current smokers, 44% reported the LHC had made them consider stopping, 29% it made them try to stop and 25% made them smoke less whilst only 1.7% and 0.7% said it made them worry less about smoking or think it acceptable to smoke. Conclusions: Our data suggest a community-based lung cancer screening programme in deprived areas positively impacts smoking behaviour, with no evidence of a 'licence to smoke' in those screened.